2012
DOI: 10.1007/s10653-012-9466-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cadmium concentrations in a population downstream: from a zinc mining area in Mae Sot District, Tak Province, Thailand

Abstract: Urinary cadmium (UCd) is a good indicator of long-term exposure to cadmium. UCd concentrations resulting from juvenile cadmium exposure in 3 sub-districts of Tak Province, Thailand, were investigated. The target population was divided by gender and into 2 age subgroups: 9-12 and 13-15 years. A total of 748 urine samples were collected and analyzed by spectrophotometer. All samples had UCd of more than 1.0 μg/g creatinine (Cr). Total UCd means among the 3 sub-districts were 1.31, 1.01, and 0.87 μg/g Cr; the Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, the level of cadmium exposure in Thai children appeared to be decreasing due to cessation of mining activity and subsequent declining environmental contamination [38]. It is therefore hoped that the renal effects associated with cadmium exposure the in local Thai children will also continue to decrease [3739]. Indeed, Swaddiwudhipong et al have reported no association between cadmium exposure and blood pressure in children [37].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the level of cadmium exposure in Thai children appeared to be decreasing due to cessation of mining activity and subsequent declining environmental contamination [38]. It is therefore hoped that the renal effects associated with cadmium exposure the in local Thai children will also continue to decrease [3739]. Indeed, Swaddiwudhipong et al have reported no association between cadmium exposure and blood pressure in children [37].…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory effects, such as declined pulmonary function or chronic respiratory symptoms, were associated with air pollution (PM) in the Maemoh district, Lampang, and Bangkok [6264]. Early renal effects from chronic cadmium exposure, reduced cord serum T4 from organochlorine exposure, and allergy risk of allergic rhinitis and atopic dermatitis from air pollution (DEPs) were found in Tak and Chiang Mai, respectively [373967]. Increased cancer risk and DNA damage, and decreased DNA repair capacity, were detected in Bangkok and the Ron Phibul district, Nakorn Sri Thammarat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum allowable limit for Cd in agricultural soils in Indonesia is still non-existent, however in some country such as China has 1.5 -4 mg kg -1 limit depending on soil pH [41], India has 3 -6 mg kg -1 [42], and the neighboring country Vietnam has 2 mg kg -1 limit [2] [43]. Europe Union has the maximum limit of 3 mg kg -1 Cd in agricultural soils [44].…”
Section: Content In Soilmentioning
confidence: 99%